2008
DOI: 10.5897/ajb08.176
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and antibiotic susceptibility pattern of Staphylococcus aureus amongst patients with urinary tract infection (UTI) in UBTH Benin City, Nigeria

Abstract: Staphylococcus aureus is one of the most widely spread human pathogen. Considering the havoc it causes on life and subsequently on the economy, it became necessary to determine its incidence and antibiogram in our environment for adequate control and treatment. Records of microbial cultures and antibiotic sensitivity test results of suspected cases of urinary tract infection (UTI) of the University of Benin Teaching Hospital (UBTH) Benin City from January 1 st to 31 st December, 2005 were retrieved and statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 6 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…This is in agreement with previous studies which had a similar finding [16,17]. However, the occurrence of 78.15% in pregnant women and 21.85% in non-pregnant women seen in our study was much higher than the 22.8% obtained by Akortha and Ibadin in 2008 [18].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous studies which had a similar finding [16,17]. However, the occurrence of 78.15% in pregnant women and 21.85% in non-pregnant women seen in our study was much higher than the 22.8% obtained by Akortha and Ibadin in 2008 [18].…”
Section: Discussionsupporting
confidence: 93%
“…In comparison to earlier studies, the current study (Akortha and Ibadin, 2008) revealed a significant increase in antibiotic resistance among microorganisms isolated from Bangladeshi patients. This may be the result of antibiotic misuse, the use of antibiotics from uncontrolled sources of production, such as those that are unknown to the user, the use of inactivated antimicrobials, antibiotic selection pressure, and a lack of quality control on some sources of antibiotics entering Bangladesh, particularly by the private sector.…”
Section: Identifying the Frequency Of Antibiotic Resistance And Antim...contrasting
confidence: 84%
“…A study conducted in Ireland concluded that 27.8% of S. aureus isolated from urine samples were MRSA [40]. Recent studies have reported the increasing prevalence of multi drug resistant S. aureus especially MRSA in UTIs [40, 41]. Among E. faecalis, 95% were resistant to amikacin, 69% to penicillin and 68% towards ofloxacin.…”
Section: Discussionmentioning
confidence: 99%